A comunicação do paciente em coma: estudo das manifestações fisiológicas dos pacientes em coma na unidade de terapia intensiva e suas possíveis respostas comunicativas - Mimura, Verusk Arruda (2018)
This present thesis is an analysis on communication of the body in coma in intensive care units. The communication process between those patients and the health staff demands constant evaluation on their perception. Recent studies have indicated possibilities of flaws in classifying patients in coma and they have questioned the excessive faith that has been placed on technological devices. Therefore, we propose here the investigation of the primary communication of patients in coma through olfaction, making use of an interdisciplinary study involving communication and health sciences. This study is in accordance with the studies of Semiotics of Culture as well as with the advances in the field of medical research which suggest changes of the established paradigm for the diagnose of those patients. The objective of this study is identifying from olfaction stimulation any probable evidence of communication of patients in coma, by reading and interpreting any possible physiological alterations such as electroencephalographic recording, blood pressure, heart rate and oxygen blood saturation, associated to the observation of subjective signs emitted by the body, from face and body expressions, searching for a possible triggering of the olfactory memory. The physiological responses of patients in coma were compared to those of outpatients. As to face the lack of meaningful statistic alterations on patients in coma, the outpatients were called to take a central role on this present study. Yet, the qualitative analysis makes it possible to imply that the primary responses delivered by the body of the patients in coma might be considered as communication when submitted to olfactory stimulation carried by the combination of other stimuli sensitive to the senses. This interdisciplinary study points to the need of creating between the fields of communication and health an essential link toward the studies of the human body. The theoretical framework was built around the following authors: A. R. Luria (1966, 1979, 1982, 1991), Oliver Sacks (1988, 2013), Edgar Morin (1973, 1996), Gerald M. Edelman (1992), Norval Baitello Jr. (1997, 2005, 2012), F. S. Machado (2006), Hawkes and Doty (2009), Jox et al. (2012), E. Delamonica (1984) among others